Collagen-1 Suppression and Fibrosis Prevention by Garcinia Mangostana L. Rind Extract: A Study on NF-κB and TGF-β1 Pathway Inhibition - Triyanta Yuli Pramana; Bambang Purwanto; Ambar Mudigdo; Suroto; Vitri Widyaningsih; Risya Cilmiaty; Brian Wasita (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Liver fibrosis is a progressive disease characterized by excessive deposition of extracellular matrix components, such as collagen-1, resulting in tissue scarring and impaired liver function. Activation of the NF-κB and TGF-β1 pathways plays a central role in fibrogenesis. Garcinia mangostana L. rind extract (GMREE) has demonstrated potential anti-fibrotic and anti-inflammatory effects in previous studies. This research investigates the ability of GMREE to suppress collagen-1 production and prevent liver fibrosis by inhibiting the NF-κB and TGF-β1 pathways in an isoniazid-induced fibrosis model in Wistar rats. Methods: Thirty-two male Wistar rats were divided into four groups: a control group, a positive control group treated with isoniazid, and two treatment groups receiving GMREE at doses of 250 mg/kg/day and 500 mg/kg/day alongside isoniazid. Serum levels of SGPT were measured as a marker of liver injury. Liver tissues were analyzed for collagen-1 deposition, and immunohistochemical assays were performed to assess NF-κB and TGF-β1 expression. Results: GMREE treatment significantly reduced serum SGPT levels (p < 0.001) and suppressed liver fibrosis, as evidenced by decreased collagen-1 deposition in the liver tissues. Immunohistochemical analysis revealed a significant reduction in NF-κB and TGF-β1 expression in the treatment groups compared to the positive control group (p < 0.05), with the 500 mg/kg/day dose showing the greatest inhibitory effects on these key fibrotic markers. Conclusion: Garcinia mangostana L. rind extract demonstrates strong anti-fibrotic properties by downregulating collagen-1 production and inhibiting the NF-κB and TGF-β1 pathways. These findings highlight GMREE as a potential therapeutic agent for the prevention and management of liver fibrosis, particularly in cases of drug-induced liver injury.